Treatment of Acute Wounds With Recombinant Human-Like Collagen and Recombinant Human-Like Fibronectin in C57BL/6 Mice Individually or in Combination - Dong, Yunqing; Zhu, Weidong; Lei, Xiaoxuan; Luo, Xin; Xiang, Qi; Zhu, Xuanru; Pan, Qiao; Jin, Panshi; Cheng, Biao (Frontiers in Bioengineering and Biotechnology, 2022)
Wound repair is accomplished by the interaction between the cells involved in the repair and the extracellular matrix (ECM). Collagen is the main component of ECM, which is involved in transduction of signal, transportation of growth factors and cytokines. Fibronectin(FN) is also an important ECM, which participates in the initiation of fibroblast cell(FC) and promotes adhesion, migration, proliferation and differentiation of target cells. Compared with natural protein, the recombinant protein prepared by artificial method has the advantages of poor immunogenicity, wide range of sources, low cost and high activity. In this study, we used recombinant human-like collagen (RHC) and recombinant human-like fibronectin (rhFN) to treat acute wounds in C57BL/6 mice individually or in combination, and explored their effects on wound healing.